Queering the Middle Ages - Burger, Glenn, 1954-; Kruger, Steven F. (Medieval cultures, 2001)
The essays in this volume present new work that, in one way or another, "queers" stabilized conceptions of the Middle Ages, allowing us to see the period and its systems of sexuality in radically different, off-center, and revealing ways